In opdracht van de minister: De Leidse conservator LJ.F. Janssen bericht Den Haag over de archeologie in Limburg tussen 1848 en 1850 (deel 1) - Verhart, Leo (Publications de la Société Historique et Archéologique dans le Limbourg, 2023)
Between 1848 and 1850, L.J.F. Janssen, curator of the National Museum of Antiquities in Leiden, made some study trips in the new province of Limburg. Initially he researched for the Minister of Internal Affairs complaints made about rather bad dealings of cultural heritage in the town Maastricht. This was followed by visiting archaeological sites, the description of the collections of connoisseurs of antiquities and he conducted some fieldwork in the province of Limburg. He reported his findings to the minister in The Hague, which resulted in the possibility to undertake some excavations in the years to follow. He mainly excavated Roman villas in cooperation with Charles Guillon, a respected notary and antiquarian from Roermond.Janssen wrote six reports for the Minister of Internal Affairs. One was published, but the other five not. These important reports are made public in this article. In this part the first three and next years the last ones. PUBLICATIONS